Clinical Phenotypes and Age-Related Differences in Presentation, Treatment, and Outcome of Heart Failure with Preserved Ejection Fraction: A Vietnamese Multicenter Research - Ngoc-Thanh-Van Nguyen; Diep Tuan Tran; Pham Le An; Sy Van Hoang; Hoai-An Nguyen; Hoa Ngoc Chau (Cardiology Research and Practice)
Background. Heart failure with preserved ejection fraction (HFpEF) is a rising health problem with heterogeneous presentation and no evidence-based treatment. While Southeast Asia reported the highest mortality and morbidity among Asian population, little is known about the Vietnamese population, including patient characteristics, prescribing pattern and mortality rate. Methods. We conducted an observational study on 477 patients diagnosed with HFpEF from seven hospitals in Southern Vietnam from January 2019 to December 2019. Results. Mean age was 67.6 (40.9% < 65 years). 62.3% were female. 82.4% were diagnosed within 5 years. Dyspnea, congestion, and hypoperfusion on admission were noted in 63.9%, 48.8%, and 4.6% of the patients, respectively. Median ejection fraction was 63%. Valvular heart disease (VHD) was the leading cause of heart failure (35.9%). 78.6% had at least two comorbidities, mostly hypertension (68.6%). 30.6% of the patients were hospitalized, with a median stay of 7.0 (4.0–10.0) days and inhospital mortality of 4.8%. Older patients (≥65 years) were more likely to be females (OR = 1.52); had multimorbid conditions (OR = 3.14), including hypertension (OR = 4.28), diabetes (OR = 1.73), coronary artery disease (CAD) (OR = 2.50), dyslipidemia (OR = 1.94), and chronic kidney disease (OR = 2.44); and were more frequently prescribed statin (OR = 3.15). Younger individuals (<65 years) were associated with higher mineralocorticoid antagonist uptake (OR = 0.52) and VHD (OR = 0,40). Prescription rate for renin-angiotensin-aldosterone system inhibitor, beta blocker, mineralocorticoid antagonist, and loop diuretic was 72.5%, 59.1%, 43.0%, and 60.6%, respectively. Four phenotypes were identified, including the lean/elderly/multimorbid; congestive/metabolic; CAD-induced; and younger/atrial fibrillation (AF)/VHD. The novel phenotype “younger/AF/VHD” exhibited high symptom burden and poor functional capacity despite being the youngest and least multimorbid. The “lean/elderly/multimorbid” phenotype demonstrated the highest symptom severity and inhospital mortality. Conclusions. Our research highlights a younger, predominantly female population with high disease burden. The four novelly identified phenotypes provide contemporary and pragmatic insights into a phenotype-guided approach, exclusively targeting the Vietnamese population.